Peningkatan Hasil Belajar Soal Cerita keliling Persegi dan Persegi Panjang Dengan Pendekatan CTL - Sri Hermaita Putri; Mardiah - Harun; Syafri - Ahmad (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by the low learning outcomes of students in learning about square and rectangular stories. The aim of the study was to describe the implementation of learning and the increase in learning outcomes around square and rectangular stories. This type of research is Classroom Action Research (CAR), using quantitative and qualitative approaches. The results of the study show that the Learning Implementation Plan of the first cycle obtained a value of 90% (B) and increased to 100% (SB) cycle II. The learning aspect of the teacher in the first cycle obtained an 80% (C) value increased to 95% (B) cycle II. While the implementation stage of the aspects of students in the first cycle scored 78% (C) increased to 90% (B) cycle II. Learning outcomes of students in the first cycle obtained an average score of 70, increasing to 85 cycles II.